2019
DOI: 10.32596/ejcm.galenos.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Management for Carotid Endarterectomy: Review Article

Abstract: Atherosclerotic carotid artery disease is responsible from 20% to 25% of ischemic stroke events. Open carotid surgery and stent insertion are two main types of treatment procedures. Carotid endarterectomy (CEA) can be performed under general anaesthesia, regional anaesthesia (interscalen block, cervical plexus block either by landmark technique or by US guidance), combination of general and regional anaesthesia, regional anaesthesia with combination of periferic block. The aim of all anesthesic techniques is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(199 reference statements)
1
2
0
Order By: Relevance
“…The results we obtained from our cases were consistent with the results of previous publications except Seidel et al [12]. As highlighted in previous publications, "right dose of the right drug placed in the right place" describes the gold standard of every peripheral block [1,14]. We thought that "right block combinations" should also be added to this philosophy while combining the regional blocks for CEA.…”
Section: Discussionsupporting
confidence: 91%
“…The results we obtained from our cases were consistent with the results of previous publications except Seidel et al [12]. As highlighted in previous publications, "right dose of the right drug placed in the right place" describes the gold standard of every peripheral block [1,14]. We thought that "right block combinations" should also be added to this philosophy while combining the regional blocks for CEA.…”
Section: Discussionsupporting
confidence: 91%
“…(8) Improved procedural outcomes are due to the advances in medical therapy, cerebral monitoring, improved timing of surgery, improved surgical techniques and the use of ultrasound guided regional techniques. (9) In this case study we found that a combined general and local anaesthetic technique worked well minimising our use of opiates and allowing prompt emergence and neurological assessment.…”
Section: Volume 19 Numbermentioning
confidence: 68%
“…These difficulties can be significantly overcome by preferring regional anesthesia (RA). Despite its negative aspects, such as requiring patient cooperation and some difficulties in pain control, RA is an excellent alternative to GEA due to its advantages, such as shortening the hospital stay and low risk of hemodynamic instability (3). However, the issue of which anesthesia method should be chosen in CEAs is still controversial.…”
Section: Introductionmentioning
confidence: 99%